2003
DOI: 10.1159/000070478
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in Peripheral Blood Eosinophils from Patients with Atopic Dermatitis by Differential Display

Abstract: To identify the genes related to atopic dermatitis (AD), we compared gene expression in eosinophils from AD patients and healthy volunteers. RNA was prepared from peripheral blood eosinophils. Gene expression was monitored by fluorescent differential display (DD) and real-time RT-PCR. Eighteen new sequences, including expressed sequence tags (ESTs), were expressed at higher levels in eosinophils from AD patients than in those from healthy volunteers. The functions of most of these genes are unknown. We found n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These studies have revealed some novel genes implicated in performing essential roles in the pathological conditions characteristic of allergic diseases (Matsumoto et al , 2004aHeishi et al 2002;Imai et al 2002;Hashida et al 2003;Nagata et al 2003;Ogawa et al 2004;Kagaya et al 2005a). A successful example of this approach has been the identification of the nuclear receptor gene family whose enhanced expression in peripheral blood eosinophils correlated with the pathological condition of AD.…”
Section: Comprehensive Gene Expression Analysis In Eosinophils From Pmentioning
confidence: 99%
“…These studies have revealed some novel genes implicated in performing essential roles in the pathological conditions characteristic of allergic diseases (Matsumoto et al , 2004aHeishi et al 2002;Imai et al 2002;Hashida et al 2003;Nagata et al 2003;Ogawa et al 2004;Kagaya et al 2005a). A successful example of this approach has been the identification of the nuclear receptor gene family whose enhanced expression in peripheral blood eosinophils correlated with the pathological condition of AD.…”
Section: Comprehensive Gene Expression Analysis In Eosinophils From Pmentioning
confidence: 99%
“…We compared gene expression in peripheral blood eosinophils from both AD patients and healthy volunteers and identifi ed some genes that were differentially expressed [12] . Some of the differentially expressed genes belonged to the human orphan nuclear receptor family, NR4A.…”
Section: Nr4a Orphan Nuclear Receptor Family In Peripheral Blood Eosimentioning
confidence: 99%
“…The analysis of genes differentially expressed between ad patients and normal individuals and between the different phases of ad may provide information on the molecular pathogenesis of the disease. To identify the genes involved in allergic diseases, we analyzed transcription profiles in peripheral blood immune cells from patients with allergic diseases, and found many genes that were differentially expressed between patients and healthy individuals (1,2). during differential display (dd) gene expression studies on peripheral blood cd3+ T cells from ad patients, we observed that the level of expression of a gene later designated coiledcoil domain containing 132, transcript variant 1 (CCDC132) was markedly higher in ad patients than in normal controls.…”
Section: Introductionmentioning
confidence: 99%